Sustainable Water Management Practices at ETUT: Innovations and Policies - Gurbanmyrat Mezilov; Dovlet Annamuradov; Perman Hojagulyyev; Aylar Gurbanova; Serdar Gedayev; Yslam Orazov (Universitas Diponegoro, 2024)
The paper delves into the water management strategies of Oguz Han Engineering and Technology University of Turkmenistan (ETUT), emphasizing sustainable practices and regulatory compliance. ETUT employs various innovative techniques like rainwater collection through rain gardens, permeable pavement, and cisterns to mitigate runoff and enhance water quality. Rainwater is stored for irrigation, reducing reliance on municipal sources and contributing to groundwater recharge. A water-recycling program repurposes rainwater and fountain water, while innovative structures promote plant growth and water conservation by condensing atmospheric moisture. The university utilizes advanced wastewater treatment methods incorporating plants and microorganisms to purify water efficiently. Complying with national regulations ensures safe drinking water provision and resource protection. Regular monitoring aids in assessing policy effectiveness, fostering continuous improvement. ETUT's commitment to sustainability and environmental stewardship is reflected in its comprehensive water conservation program, fostering a culture of innovation and responsibility within the university community.